Identification of novel transcriptional regulators of Zat12 using comprehensive yeast one‐hybrid screens. Issue 4 (14th April 2016) - Ben Daniel, Bat‐Hen; Cattan, Esther; Wachtel, Chaim; Avrahami, Dorit; Glick, Yair; Malichy, Asaf; Gerber, Doron; Miller, Gad
Abstract : To appropriately acclimate to environmental stresses, plants have to rapidly activate a specific transcriptional program. Yet, the identity and function of many of the transcriptional regulators that mediate early responses to abiotic stress stimuli is still unknown. In this work we employed the promoter of the multi‐stress‐responsive zinc‐finger protein Zat12 in yeast one‐hybrid (Y1H) screens to identify early abiotic stress‐responsive transcriptional regulators. Analysis of Zat12 promoter fragments fused to luciferase underlined an approximately 200 bp fragment responsive to NaCl and to reactive oxygen species (ROS). Using these segments and others as baits against Y1H control or stress Arabidopsis prey libraries, we identified 15 potential Zat12 transcriptional regulators. Among the prominent proteins identified were known transcription factors including bZIP29 and ANAC91 as well as unknown function proteins such as a homolog of the human USB1, a U6 small nuclear RNA (snRNA) processing protein, and dormancy/auxin‐associated family protein 2 (DRM2). Altered expression of Zat12 during high light stress in the knockout mutants further indicated the involvement of these proteins in the regulation of Zat12 . Using a state of the art microfluidic approach we showed that AtUSB1 and DRM2 can specifically bind dsDNA and were able to identify the preferred DNA‐binding motif of all four proteins. Overall, the proteins identified in this work provide an important start point for charting the earliest signaling network of Zat12 and of other genes required for acclimation to abiotic stresses.